2015
DOI: 10.1590/s0100-83582015000400001
|View full text |Cite
|
Sign up to set email alerts
|

SEED DORMANCY BREAKING TREATMENTS FORAFRICAN PURSLANE (Zaleya pentandra)

Abstract: -Understanding the mechanisms involved in releasing seed dormancy is crucial for effective plant management and renewal of species in the arid zone. Zaleya pentandra is an emerging invasive weed of the arid areas of Pakistan. We investigated the effects of different dormancy breaking treatments on the germination of Z. pentandra seeds. Seeds were treated with hot water (by placing them in boiling water for 5, 15, 30, 60, 90, 120, and 150 min), dry heat (by placing them in a preheated oven at 70 o C for 1, 2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They noted that the different concentrations used had variable responses among the varieties. Munawar et al (2015) reported that treatment of seeds with dry heat completely suppressed germination. However, Seshu and Dadlani (1991) reported that dry heat was effective in breaking dormancy on rice seed.…”
Section: Discussmentioning
confidence: 99%
“…They noted that the different concentrations used had variable responses among the varieties. Munawar et al (2015) reported that treatment of seeds with dry heat completely suppressed germination. However, Seshu and Dadlani (1991) reported that dry heat was effective in breaking dormancy on rice seed.…”
Section: Discussmentioning
confidence: 99%
“…The seeds of Ruschia spinosa and Drosanthemum asperulum germinate fast, whereas R. tenella seeds germinate gradually. Delayed germination has been reported in Sesuvium portulacastrum ( Martínez et al., 1992 ; Lonard and Judd, 1997 ), Trianthema portulacastrum ( Tanveer et al., 2013 ), Zaleya pentandra ( Munawar et al., 2015 ), and all of them have a thick seed coat.…”
Section: Discussionmentioning
confidence: 99%
“…Factors like lack of natural predators, habitat degradation, adaptive nature of alien environments, inherited plant attributes for rapid growth, high seed output, diverse seed dispersal modes, phenotypic plasticity, genetic diversity, resistance to various environmental stresses, staggered seed dormancy and allelopathic nature has favored the invasion potential of these weed species in Pakistan (Marwat et al, 2010;Ali et al, 2011Ali et al, , 2012Nasim and Shabbir, 2012;Rashid et al, 2014;Munawar et al, 2015). These weeds pose threat to abundance and diversity of local flora and fauna, adversely effecting ecosystem functioning (Khan et al, 2011;Bajwa et al, 2016).…”
Section: Invasive Weedsmentioning
confidence: 99%